Matlab Circuit Simulation Model Based on SiC MOSFET Non-linear Capacitor CGD - Xing DU; Cuixia WANG; Youling YU; Jiangfeng WU; Kun LIU; Sisi LI (机车电传动)
Based on Matlab and Simulink, a modeling method for non-linear devices was proposed. Taking the SiC MOSFET of CREE company C2M0080120D as an example, the equivalent circuit model of its nonlinear capacitance CGD was established. By using the curve fitting method, the non-linear capacitance characteristics of power devices which are not easy to realize in Simulink can be characterized. Compared with datasheet, the accuracy of the model was 97.44%. The accuracy of the model was validated.